Beneath the Finance–Growth Nexus: The Case of Japan's Post-World War II Commercial Banking. Issue Volume 15:Issues 1(2016) (2nd January 2016) - Inaba, Kei-Ichiro
ABSTRACT: For most of the post-World War II period, Japan's finance–growth nexus did not benefit greatly from the information-producing and monitoring activities of commercial banks. This contradicts the famous Main Bank thesis. Regulations on direct finance and competitive restrictions on banking effectively liberated the banks from having to develop their informational activities. These institutional factors also enabled the banks to extract regulatory and informational rents from client companies. Bank regulators were motivated to stick to the status quo without reforming such commercial banks. On an aggregate basis over the period 1965–96, corporate profitability negatively correlated with bank loan dependency, and liquidity constraints impacted on corporate finance.